The Role of Leadership in Ruarl Head on Rural Finacial Management (A Case Study in Seretan Timu Rural Lembean Timur District Minahasa Regency) . - Manopo, Stefano Oktavian; Rumapea, Patar; Pangkey, Masje (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT   The success of the village government can run smooth  and well because it is supported by  many factors, one important factor is the village finances because it is impossible for the village to  be able to carry out  the village  administration effective and efficient  without adequate financial  support.  This  is  due  to  the  financial  capacity  of  the  village  depends  on  the  size  and  variety  of  sources of income as financial resources are owned by the village. Therefore, the leadership of the  village  head  and  village,  excavation  and  management  of  the  financial  resources  of  the  village  should be sought as optimal as possible to reach the village government administration efficient  and effective as well as adhering to the Regulation of the  Minister of Home Affairs Number 37  Year  2007  regarding  the  General  Guidelines  for  Financial  Management  village.  The  aim  of  the  research  is  to  describe,  analyze  and  find  out  how  the  village  head's  leadership  role  in  the  management of village finances (Case  Study in the village of Seretan Timu drag troughs Minahasa  District of East Lembean).   This  study  used  qualitative  data  analysis  method  presented  descriptive  with  purposive  sampling  technique  of  sampling  /  sample  aiming  the  number  of  informants  there  are  fifteen  informants.   From  the  results  of  existing  research,  the  village  head's  leadership  role  in  the  financial  management  of  the  village  has  not  been  complete  worked  well  because  there  is  no  budget  is  unclear or data were incomplete, income and expenses can not be measured because it is not in  accordance with the conditions of the village and village regulations only kinship systems but with  all   the   shortcomings   of   existing   good   cooperation   with   the   village   officials   to   seek   the  implementation of the financial management of the village with transparancy,  accountability and  participation.   Keywords: The Role of Leadership, Financial Management Rural